The Cave, by José Saramago: the impact of globalization in the world of work and education (Research, Society and Development, 2019)
This paper aims to demonstrate the importance of reading the universal classics to facilitate the comprehension of nowadays problems, especially those related to the work realm and in consequence affecting the education, impacted by the globalization process. The reading of classics such as The Cave by José Saramago, enables the enhancing of the reading skills and favors knowledge widening in many diverse areas. The novel addresses the impact of globalization in the life of a citizen who was excluded from the labor market because he was unprepared for the demandings of the present time. A thorough bibliographic research will be performed as a methodology. From the studies of a classic, the teaching of humanities will be sought, enabling thus the opening for the magical, the poetic and the ludic as tools for personal and professional cultural enrichment. In this sense, Literature opens ways for the interdisciplinarity, allowing each teacher to explore the inherent aspects related to his or her field of expertise and contributing with a dialog promoting activity with other subjects, exploring the same literary text with more than one point of view, contributing to promote a kind of teaching where the integral development of the citizen is intended.